Ergonomic of School Facilities and Infrastructure to Support Effective Schools - Ghozali, Muhammad; Rizqiyana (Proceeding International Conference on Religion, Science and Education, 2022)
The placement of the blackboard (LCD), the use of lighting, the size of the seats, study desks and others in schools are very important for the comfort, health and safety of students and teachers. One way that can be taken is through knowledge of ergonomic principles. The purposes of writing are: (1) reviewing and knowing the ergonomics principles of school facilities and infrastructure; (2) examine the importance of ergonomic principles in schools. Through a literature review, relevant ergonomic principles are explored to be applied to school facilities and infrastructure. The results of the study show that there are still educational staff and educators who currently do not know and understand the ergonomics principles of facilities and infrastructure, but school facilities and infrastructure are in accordance with the standards determined by the relevant education office. Through this paper, teachers are required to know about ergonomics theory for classroom facilities and infrastructure and can apply it in learning so that learning can run effectively and efficiently.